Peramalan Terjadinya Gempa Bumi Tektonik untuk Wilayah Pulau Nias Menggunakan Metode Distribusi Weibull dan Eksponensial - Malau, Nya Daniaty; Sitepu, Mester (EduMatSains, 2016)
Nias Island is an island located west of North Sumatra dipesisir which has a fairly high level of seismicity. This paper discusses the problem of forecasting the occurrence of tectonic earthquakes for the island of Nias, located on the site: 0º19LU - 1º82LU and 96.97 BTº- 98.53ºBB. By using the data a powerful earthquake that caused damage. Tectonic earthquake forecasting is done with method 3 parameter Weibull distribution, two parameter Gumbel distribution and exponential distribution of parameter 1. using the data as much as 47 damaging earthquakes from year 1960 to 2012, which is a major earthquake (mainshock) the magnitude of 6.0 - 9.1 SR. To calculate the waiting time distribution forecasting using a third used the software Mathematica for Windows version 8.0. Making the program requires data - input data relating to waiting times of earthquakes in the past to the present. By making this prediction program to predict the timing of the tectonic earthquake in Nias Island.So predictable subsequent tectonic earthquake in Nias island territory will occur on September 4, 2013 when predicted using the Weibull distribution with three parameters, dated April 5, 2013 if the forecast using the Gumbel distribution with two parameters and dated September 4, 2013 when predicted using the method of distribution exponential with a parameter.